1996
DOI: 10.1021/ja961621o
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intercatechol Cross-Links in Insect Cuticle by Solid-State Carbon-13 and Nitrogen-15 NMR

Abstract: Solid-state NMR has been used to detect an intercatechol covalent bond in sclerotized cuticle of the tobacco hornworm (Manduca sexta). Rotational-echo, double-resonance (REDOR) 13C and 15N NMR, in combination with 1H−13C dipolar modulation and 15N−15N dipolar restoration at the magic angle, were used to examine hornworm pupal exuviae labeled with β-[15N]alanine and either [β-13C]dopamine or [α-13C,15N]dopamine. The REDOR spectra showed the incorporation of N-β-alanyldopamine into insect cuticle by the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…Solid-state NMR measurements showed that isotopically labeled dopamine and b-alanine are incorporated into pupal cuticle of M. sexta by formation of covalent linkages between the imidazole ring of histidine residues and the aromatic ring or the sidechain b-position in dopamine; occurrence of linkages to chitin and to the b-alanyl residue of NBAD was also indicated (Schaefer et al, 1987;Kramer et al, 1989Kramer et al, , 1995Christensen et al, 1991;Merrit et al, 1996).…”
Section: Adduct Formation During In Vivo Sclerotizationmentioning
confidence: 99%
“…Solid-state NMR measurements showed that isotopically labeled dopamine and b-alanine are incorporated into pupal cuticle of M. sexta by formation of covalent linkages between the imidazole ring of histidine residues and the aromatic ring or the sidechain b-position in dopamine; occurrence of linkages to chitin and to the b-alanyl residue of NBAD was also indicated (Schaefer et al, 1987;Kramer et al, 1989Kramer et al, , 1995Christensen et al, 1991;Merrit et al, 1996).…”
Section: Adduct Formation During In Vivo Sclerotizationmentioning
confidence: 99%
“…The resulting spectrum has sidebands spaced at the actual spinning speed but an intensity envelope identical to that taken at a quarter of the spinning speed. The extendability of this pulse sequence distinguishes it from methods that enhance the sidebands by dipolar decoupling for a fraction of the rotor cycle (14,22).…”
Section: N-fold Amplification Of the Dipolar Evolutionmentioning
confidence: 99%
“…REDOR has found additional application in detection of formation of chemical bonds [7,8] and in resonance assignment of small peptides [9]. The wide use of REDOR is primarily due to the relative simplicity and robustness of its pulse sequence and data analysis.…”
Section: Introductionmentioning
confidence: 99%